Radiation hardness of AlAs/GaAs-based resonant tunneling diodes - Belyaev, A.A.; Belyaev, A.E.; Konakova, R.V.; Vitusevich, S.A.; Milenin, V.V.; Soloviev, E.A.; Kravchenko, L.N.; Figielski, T.; Wosinski, T.; Makosa, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The total dose effects of ⁶⁰Co γ-radiation on the electrical properties of double-barrier Resonant Tunneling Diodes have been studied. The devices manifest enhanced radiation hardness and conserve their operating parameters up to doses of 2×10⁹ rad. It is shown that all changes in the current-voltage characteristics stem from the effect of ionizing radiation on the undoped layers. The radiation-stimulated diffusion of the heteropair components in the contact region is shown to be important for the voltage drop distribution.